2012
DOI: 10.1016/j.placenta.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory molecules are released from the first trimester and term placenta via exosomes

Abstract: The semiallogenic fetus is tolerated by the maternal immune system through control of innate and adaptive immune responses. Trophoblast cells secrete nanometer scale membranous particles called exosomes, which have been implicated in modulation of the local and systemic maternal immune system. Here we investigate the possibility that exosomes secreted from the first trimester and term placenta carry HLA-G and B7 family immunomodulators. Confocal microscopy of placental sections revealed intracellular colocaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
134
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 62 publications
6
134
0
3
Order By: Relevance
“…92 However, a more recent study showed that B7 immunomodulatory molecules and HLAG5 are secreted via exosomes from early and term placentas. 93 This study offered a novel perspective in which human placenta-derived exosomes may have served directly as key mediators of maternal immunotolerance to the semiallogeneic fetus. The identification of these key immunoregulatory proteins bound to placenta-derived exosomes supports the fact that exosomes have an immunomodulatory role in preventing the degradation of invading trophoblastic cells by inducing maternal T-cell apoptosis, which could play a key role in maternal complications, such as PE, fetal rejection, and intrauterine growth restriction.…”
Section: Role Of Placenta-derived Exosomes In Maternal Immunomodulationmentioning
confidence: 99%
“…92 However, a more recent study showed that B7 immunomodulatory molecules and HLAG5 are secreted via exosomes from early and term placentas. 93 This study offered a novel perspective in which human placenta-derived exosomes may have served directly as key mediators of maternal immunotolerance to the semiallogeneic fetus. The identification of these key immunoregulatory proteins bound to placenta-derived exosomes supports the fact that exosomes have an immunomodulatory role in preventing the degradation of invading trophoblastic cells by inducing maternal T-cell apoptosis, which could play a key role in maternal complications, such as PE, fetal rejection, and intrauterine growth restriction.…”
Section: Role Of Placenta-derived Exosomes In Maternal Immunomodulationmentioning
confidence: 99%
“…In agreement with this, in myeloma cells mHLA-G is also released from the cell membrane in microparticles. 35 These findings suggest that quantification of sHLA-G may be clinically useful and more informative than analysis of the surface of tumor cells.…”
mentioning
confidence: 94%
“…Indeed despite Vacchio and Hodes [31] demonstrating that fetal FasL expression induced CD8 + T-cell tolerance to the fetal antigen H-Y during pregnancy, and that the loss of placental FasL is associated with increased fetal loss and thus small litter sizes [32], Chaouat and Clark suggested that apoptosis of T-cells in allopregnancies were mediated via mechanisms other than Fas + /FasL + [33]. Those alternate mechanisms would no doubt include TRAIL/TRAIL receptors (DR4 and DR5) and PD-L1/PD-1, another immune modulating moiety known to be expressed on exosomes [34].…”
Section: Discussionmentioning
confidence: 99%